Prepubertal chrysin exposure upregulates either AR in male ventral prostate or AR and ERα in Skene's paraurethral gland of pubertal and adult gerbils - Ribeiro, Naiara C.S. (2018)
Chrysin is a plant-derived polyphenol that has the potential to increase endogenous testosterone levels both by inhibiting the aromatase enzyme and by stimulating testicular steroidogenesis. The effects of chrysin on the prostate are unknown, especially during its development and functional maturation. Thus, the aim of this study was to evaluate the effects of chrysin prepubertal exposure on the male and female prostates of both pubertal and adult gerbils. To evaluate the possible androgenic responses of chrysin, gerbils were also exposed to testosterone. Male and female gerbils were exposed to chrysin or to testosterone cypionate from postnatal day 15 to 42. Male and female gerbils were euthanized at either 43 days or 90 days age. The prostates were collected for biometrical, morphological and immunohistochemical analysis. The results showed that prepubertal exposure to chrysin had differential effects on the prostate of both pubertal and adult animals. The prostates of male and female pubertal gerbils showed no histological alterations, although there was increased frequency of androgen receptor (AR) in males and females, and estrogen receptor alpha (ERα) in females. Adult males and females presented developed prostate glands, with higher cell proliferative rate. In addition, AR and ERα frequency remained high in the prostate of adult animals. These results demonstrated that prepubertal exposure to chrysin disrupts steroid receptors regulation in the prostate, potentiating the response of this gland to the biological effects of endogenous steroids. In this context, excessive consumption of phytoestrogens during the critical stages of development should be considered with caution.